2020
DOI: 10.1002/cncr.32666
|View full text |Cite
|
Sign up to set email alerts
|

Survival of African American and non‐Hispanic white men with prostate cancer in an equal‐access health care system

Abstract: Background African American (AA) men in the general US population are more than twice as likely to die of prostate cancer (PC) compared with non‐Hispanic white (NHW) men. The authors hypothesized that receiving care through the Veterans Affairs (VA) health system, an equal‐access medical system, would attenuate this disparity. Methods A longitudinal, centralized database of >20 million veterans was used to assemble a cohort of 60,035 men (18,201 AA men [30.3%] and 41,834 NHW men [69.7%]) who were diagnosed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
102
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 99 publications
(108 citation statements)
references
References 30 publications
6
102
0
Order By: Relevance
“…It is gratifying that this work by Riviere et al 1 validates work by our group and others that over a decade ago demonstrated that socioeconomic status and access to health care explained the differences in lower treatment rates and poorer outcomes noted among AA men with PCa 2‐4 …”
supporting
confidence: 83%
See 3 more Smart Citations
“…It is gratifying that this work by Riviere et al 1 validates work by our group and others that over a decade ago demonstrated that socioeconomic status and access to health care explained the differences in lower treatment rates and poorer outcomes noted among AA men with PCa 2‐4 …”
supporting
confidence: 83%
“…We would like to congratulate Riviere et al on their study of longitudinal data from 60,035 men who were diagnosed with prostate cancer (PCa) between 2000 and 2015, 1 which highlighted that access to care is an important determinant of racial inequity. In their study, African American (AA) men who were diagnosed with PCa in the Veterans Affairs health system did not appear to present with more advanced disease or to experience worse outcomes compared with non‐Hispanic white men.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…We would like to thank Lundon et al and Hoge et al for their insightful letters and research contributions to this field 1,2 . Our work 3 has built on a large body of literature suggesting that socioeconomic factors and access to medical care are the primary drivers of poorer outcomes for African American men with prostate cancer. Our study added to this work by pointing toward a solution that is working in practice throughout the United States, suggesting that poorer outcomes for African American men with prostate cancer do not need to be a foregone conclusion.…”
mentioning
confidence: 99%